ANALISIS TINGKAT KESEJAHTERAAN DAN DETERMINAN KESEJAHTERAAN RUMAHTANGGA PENGRAJIN KULIT DI DUSUN MANDING, DESA SABDODADI, KECAMATAN BANTUL, KABUPATEN BANTUL, PROVINSI DAERAH ISTIMEWA YOGYAKARTA (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
This study aims to examine the level of welfare of leather craftsmen in Manding Village, Sabdodadi District, Bantul Regency, Special Region of Yogyakarta (DIY). Tourism in Bantul Regency has increased the number of visitors every year. In Bantul Regency there is the largest and only center for the leather product industry in the Province of DIY. This researcher examines the level of welfare of families who work as leather craftsmen in Manding Village. This study aims to determine whether the existence of the leather industry affects the welfare of craftsmen in terms of 8 welfare approaches based on indicators according to (Central Bureau of Statistics, 2015), namely: population, health and nutrition, education, employment, and consumption patterns, housing and the environment, poverty, as well as other social. The analytical tools used were the F test (Annova) and T test. The results showed that the level of family welfare between the prosperous was moderate and the prosperous was high. Gender, number of dependents, marital status, and asset ownership have a significant effect on the level of family welfare. While the length of work has no significant effect on the level of welfare..